ANALISIS PARTISIPASI PROGRAM ASURANSI NELAYAN MANDIRI TERPERCAYA DI KOTA SIBOLGA - Nur Aisyah; Muhammad Syukri Albani Nasution; Ahmad Muhaisin B Syarbaini Tanjung (JURNAL LENTERA BISNIS, 2024)
The purpose of this research is to analyse the participation of the trusted independent fishermen insurance program in sibolga city. Descriptive qualitative research type. Data collection methods are observation, interview and documentation. Information in this research totalled 5 people from small fishermen and traditional fishermen and the main informant in this research was the sibolga city marine and fisheries office. The number of fishermen who participated in the independent fisherman insurance programme in sibolga city amounted to 800% of fishermen or 69% of this programme recorded since 2012 and this is the first life insurance provided to fishermen. While the number of fishermen who do not participate in the independent fishermen insurance programme is 359 fishermen or 31%. The reason for fishermen who do not participate in the independent fishermen's insurance programme is because fishermen think that there are many cases of fraudulent insurance and fishermen are wary of the programme, then low public knowledge of the independent fishermen's insurance programme, besides that they also think that by following the insurance, they pray for us to be harmed in business. Whereas this government programme is very helpful to the community in the event of accidents and unwanted events when sailing for fishing.